Kinetic and mechanistic characterization of the Sphingomyelinases D from Loxosceles intermedia spider venom - de Andrade, S. A.; Murakami, M. T.; Cavalcante, D. P.; Arni, R. K.; Tambourgi, D. V. (Elsevier B.V., 2006)
Envenomation by arachnids of the genus Loxosceles leads to local dermonecrosis and serious systemic toxicity mainly induced by sphingomyelinases D (SMase D). These enzymes catalyze the hydrolysis of sphingomyelin resulting in the formation of ceramide-phosphate and choline as well as the cleavage of lysophosphatidyl choline generating the lipid mediator lysophosphatidic acid. We have, previously, cloned and expressed two functional SMase D isoforms, named P1 and P2, from Loxosceles intertnedia venom and comparative protein sequence analysis revealed that they are highly homologous to SMase I from Loxosceles laeta which folds to form an (alpha/beta)(8) barrel. In order to further characterize these proteins, pH dependence kinetic experiments and chemical modification of the two active SMases D isoforms were performed. We show here that the amino acids involved in catalysis and in the metal ion binding sites are strictly conserved in the SMase D isoforms from L. intermedia. However, the kinetic studies indicate that SMase P1 hydrolyzes sphingomyelin less efficiently than P2, which can be attributed to a substitution at position 203 (Pro-Leu) and local amino acid substitutions in the hydrophobic channel that could probably play a role in the substrate recognition and binding. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Loxosceles venoms; Sphingomyelinase D; sphingomyelin; kinetic parameters; Structure